Inhibitory Role of an Aeromonas hydrophila TIR Domain Effector in Antibacterial Immunity by Targeting TLR Signaling Complexes in Zebrafish - Tang, Huai-ping; Huang, Chen; Hu, Chong-bin; Li, Hao; Shao, Tong; Ji, Jian-fei; Bai, Jun; Fan, Dong-dong; Lin, Ai-fu; Xiang, Li-xin; Shao, Jian-zhong (Frontiers in Microbiology, 2021)
The Toll/interleukin-1 receptor (TIR) domain is a structural unit responsible for the assembly of signal protein complexes in Toll-like receptor (TLR) and interleukin-1 receptor signaling pathways. TIR domain homologs are found in a considerable number of bacteria and enhance bacterial infection and survival in host organisms. However, whether TIR domain homologs exist in Aeromonas hydrophila, a ubiquitous waterborne bacterium in aquatic environments, remains poorly understood. In this study, a TIR domain protein (TcpAh) was identified from A. hydrophila JBN2301. TIR domain of TcpAh is highly homologous to the counterpart domains in TLRs and myeloid differentiation factor 88 (MyD88). The zebrafish infected with mutant A. hydrophila with tcpAh deletion had a remarkably lower mortality than those infected with the wild-type strain. This result suggests that TcpAh is a crucial virulence factor for A. hydrophila infection. TcpAh exhibited a strong ability to associate with MyD88, tumor necrosis factor receptor-associated factor 3 (TRAF3) and TRAF-associated NF-κB activator-binding kinase 1 (TBK1) in TIR–TIR, TIR–Death domain (DD), and other alternative interactions. This finding suggests that TcpAh extensively participates in MyD88 and TIR domain-containing adapter inducing interferon (IFN)-β (TRIF) signaling pathways downstream TLRs. Consequently, CD80/86 expression was suppressed by TcpAh via attenuating TLR-stimulated NF-κB activation, which ultimately led to the impairment of the major costimulatory signal essential for the initiation of adaptive humoral immunity against A. hydrophila infection. We believe that this study is the first to show a previously unrecognized mechanism underlying A. hydrophila escape from host antibacterial defense by intervening CD80/86 signal, which bridges innate and adaptive immunity. The mechanism will benefit the development of therapeutic interventions for A. hydrophila infection and septicemia by targeting TcpAh homologs.